Development of In-Situ Poled Nanofiber Based Flexible Piezoelectric Nanogenerators for Self-Powered Motion Monitoring - Minjung Kim; Vignesh Krishnamoorthi Kaliannagounder; Afeesh Rajan Unnithan; Chan Hee Park; Cheol Sang Kim; Arathyram Ramachandra Kurup Sasikala (Applied Sciences, 2020)
Energy harvesting technologies have found significant importance over the past decades due to the increasing demand of energy and self-powered design of electronic and implantable devices. Herein, we demonstrate the design and application of in situ poled highly flexible piezoelectric poly vinylidene fluoride (PVDF) graphene oxide (GO) hybrid nanofibers in aligned mode for multifaceted applications from locomotion sensors to self-powered motion monitoring. Here we exploited the simplest and most versatile method, called electrospinning, to fabricate the in situ poled nanofibers by transforming non-polar α-phase of PVDF to polar β- phase structures for enhanced piezoelectricity under high bias voltage. The flexible piezoelectric device fabricated using the aligned mode generates an improved output voltage of 2.1 V at a uniform force of 12 N. The effective piezoelectric transduction exhibited by the proposed system was tested for its multiple efficacies as a locomotion detector, bio-e-skin, smart chairs and so on.